2007
DOI: 10.1111/j.1472-8206.2007.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of drug‐metabolizing enzymes CYP2D6, CYP2C9, CYP2C19 and CYP3A5 in the Greek population

Abstract: The aim of the present study was to determine the prevalence of the most common allelic variants of the polymorphic cytochrome P450 (CYP) enzymes CYP2D6, CYP2C9, CYP2C19 and CYP3A5 and to predict the genotype frequency for each polymorphism in the Greek population. DNA isolated from peripheral blood samples derived from 283 non-related Greek ethnic subjects was used to determine the frequency of CYP2D6*3, CYP2D6*4, CYP2C9*2, CYP2C9*3 and CYP3A5*3 allelic variants by the polymerase chain reaction (PCR)-restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
72
3
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 48 publications
13
72
3
5
Order By: Relevance
“…Highly similar frequencies were observed for German, Finnish, Swedish and Greek populations [2,7,11,14,17,22]. Interestingly, the allelic frequencies described in our work are not significantly different from the ones published for the Baltic Sea area.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Highly similar frequencies were observed for German, Finnish, Swedish and Greek populations [2,7,11,14,17,22]. Interestingly, the allelic frequencies described in our work are not significantly different from the ones published for the Baltic Sea area.…”
Section: Resultssupporting
confidence: 84%
“…Gene variants of CYP3A5 are responsible for major individual differences in enzymatic activity, strongly influencing pharmacokinetics and bioavailability of an array of drugs with a narrow therapeutic window, as well as the individual response to the drug therapy [2,5,15]. The most frequent single nucleotide polymorphism (SNP) of functional importance in the CYP3A5 gene is the A to G transition in intron 3 at position 6986 (CYP3A5*3) [17].…”
Section: Introductionmentioning
confidence: 99%
“…These include Brazil, 35 Iran, 36,37 East Asia, 38 Ghana, 39 United States Ashkenazi Jews, 40 Greece, 41 Mexican Americans, 42 Bolivia, 43 Israel, 44 Malaysia, 45 Egypt, 46 and whites of European descent. 47 However, these studies were limited to a small number of deficiency alleles and did not include the *17 gain-of-function allele.…”
mentioning
confidence: 99%
“…Pharmacogenetic studies have revealed the essence of polymorphism in drug metabolizing enzymes, transporters and receptors which contribute to variable drug response as per the individual's genetic makeup (Eichelbaum et al, 2006). CYP3A5 is forms are responsible for metabolizing about 50% of all clinically approved drugs (Arvanitidas et al, 2007). Thus polymorphism of CYP family may have most impact on the fate of these and other therapeutic drugs whose metabolism they regulate.…”
Section: Discussionmentioning
confidence: 99%